Glycemia Risk Index: A New Metric to Rule Them All? - Gonzalo Diaz Soto; Paloma Pérez López; Pablo Fernández Velasco; Pilar Bahillo Curieses (Diabetology)
The Glycemia Risk Index (GRI) aims to summarize the overall quality of a patient’s glycemic control in a single number, and it is calculated from the hypo- and hyperglycemia times from continuous glucose monitoring, weighted by coefficients. Despite its recent appearance in 2022, this new parameter has strong international support, with almost half a hundred indexed articles already incorporating this metric into their studies. The following is a breakdown of the main papers that have used GRI, divided according to the type of treatment used, the population studied, the type of diabetes, its association with other parameters, and its relationship with chronic complications and the quality of life of people living with diabetes.